Periodic low-power communication technology scheme for large-scale transmission line condition monitoring sensor network - Yabo ZHAN; Qian XU; Jun LI; Zhen ZONG (Dianxin kexue)
In order to realize the purpose of low energy consumption, long service life and green development of transmission line monitoring, a periodic low-power communication technology scheme of large-scale transmission line condition monitoring sensor network was proposed.According to the networking characteristics of sensor networks in large-scale transmission line condition monitoring networks and the characteristics of node operation condition conversion, sleep timers were set to make the communication nodes of sensor networks switch between initialization, sleep and activation states in a periodic operation mode.The communication nodes entered the sleep state when there was no transmission demand for transmission line condition monitoring data, so as to save communication energy consumption.Sink nodes in sensor networks used gradients to create uplink routes and source routes to create downlink routes.Based on the number of hops and residual energy, sink nodes transmitted uplink and downlink routing data packets, to reduce node energy consumption and prolong communication running time.Experiments show that after the large-scale transmission line condition monitoring sensor network applies the technical solution, the communication energy consumption is significantly reduced, the running time is significantly prolonged, and the data transmission performance of the monitoring sensor network is not affected, and the service life of the monitoring sensor network is prolonged.